Comparing the immunogenicity of mRNA and non-mRNA COVID-19 vaccines: a scoping review - Wei Tan, Kang; Mahendran, Ashwini; Khoo Si Mei, Samantha; Radhakrishnan, Ammu Kutty; Bhuvanendran, Saatheeyavaane (Faculty of Medicine, 2026)
For the past five years, the Coronavirus disease (2019 COVID-19) has spread alarmingly, challenging the economy and public health. The COVID-19 mRNA vaccines, such as Pfizer-BioNTech’s BNT162 and Moderna’s mRNA-1273, were developed in a short space of time and were the first mRNA vaccines approved by the United States Food and Drug Administration (US FDA) for Emergency Use Authorization (EUA). In phase II trials, the BNT16b2 vaccine was reported to have 91.3% efficacy against COVID-19, while the mRNA-1273 vaccine showed a slightly higher (94.1%) efficacy against COVID-19 in phase III trials. Both mRNA vaccines are reported to be safe and effective against COVID-19 and have an acceptable adverse event profile. The analysis from this scoping review suggests that the efficacy of the mRNA vaccines was superior to non-mRNA vaccines, which is based on the vaccine efficacy (VE) and antibody response analysis. Further analysis of the mRNA vaccines showed that the Moderna (mRNA-1273) vaccine had higher efficacy compared to the BioNTech, Pfizer (BNT1262b) vaccine. However, the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) appears to undergo frequent mutations in its spike protein gene, posing substantial public health concerns as even fully vaccinated individuals can succumb to the newer variants of the COVID-19 virus, warranting further investigation